2016
DOI: 10.17516/1997-1389-2016-9-1-63-74
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Biocompatibility of Poly-3- Hydroxybutyrate-co-3-Hydroxyvalerate/Poly-ε- Caprolactone Blends

Abstract: Blends consisting of the poly-3-hydroxybutyrate-co-3-hydroxyvalerate (PHBV) copolymer and poly-ε-caprolactone (PCL) were used to prepare polymer films by casting solution technique. The structure and physical-mechanical, and biological properties of the films were examined as influenced by DOI: 10.17516/1997DOI: 10.17516/ -1389DOI: 10.17516/ -2015 поли-3-гидроксибутират-3-гидроксивалерат, поли-ε-капролактон, смеси полимеров, биополимеры, биосовместимость.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…Closed pores affect the mechanical strength of a material, and their abundance in the blend film (PHBH/PCL) compared to PHBH film (Figure C,D) potentially contributes to the lower Young’s modulus of the blend. Also, the lower Young’s modulus of the PHBH/PCL blend compared with that of pure PHBH ( p = 0.000) agreed with data reported for blends of PCL and PHBH, , as well as the blends of PCL and some other PHAs. ,, However, Katsumata et al reported occasional increases in Young’s modulus when small amounts of PCL were added to poly­(3-hydroxybutyrate) (PHB) and PHBH. This was not observed in our study at the PCL ( M n 10 kDa) contents tested.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Closed pores affect the mechanical strength of a material, and their abundance in the blend film (PHBH/PCL) compared to PHBH film (Figure C,D) potentially contributes to the lower Young’s modulus of the blend. Also, the lower Young’s modulus of the PHBH/PCL blend compared with that of pure PHBH ( p = 0.000) agreed with data reported for blends of PCL and PHBH, , as well as the blends of PCL and some other PHAs. ,, However, Katsumata et al reported occasional increases in Young’s modulus when small amounts of PCL were added to poly­(3-hydroxybutyrate) (PHB) and PHBH. This was not observed in our study at the PCL ( M n 10 kDa) contents tested.…”
Section: Resultssupporting
confidence: 78%
“…Also, the lower Young's modulus of the PHBH/PCL blend compared with that of pure PHBH (p = 0.000) agreed with data reported for blends of PCL and PHBH, 17,42 as well as the blends of PCL and some other PHAs. 41,49,50 However, Katsumata et al 39 reported occasional increases in Young's modulus when small amounts of PCL were added to poly(3- hydroxybutyrate) (PHB) and PHBH. This was not observed in our study at the PCL (M n 10 kDa) contents tested.…”
Section: Release Ofmentioning
confidence: 99%
“…When the concentration of PCL or PLA in the blend is increased, samples become more compact, showing a more dense morphology with no indications of phase separation. Similar results were previously reported in blends made with PCL [34]. From these observations, it can be concluded that blending with high contents of PCL and PLA mixed with PHBV forms homogeneous and dense microstructures, contributing to obtaining improved mechanical properties with respect to neat PHBV.…”
Section: Morphological Analysis and Wettabilitysupporting
confidence: 88%
“…This is while blending could reduce the final cost associated with the use of expensive and scarcely available PHBH. So far, blends of PHBH have been considered with PLA [107][108][109], polycaprolactone (PCL) [110][111][112][113][114], polycarbonate (PC) [115], poly(methyl methacrylate) (PMMA) [116], poly (vinyl alcohol) (PVA) [117] and polystyrene (PS) [118]. Blends of PHBH with PLA and PCL, however, have been the most commonly used systems.…”
Section: Commonly Used Blending Polymersmentioning
confidence: 99%